Effect of age and castration method on neurohormonal, and electroencephalographic stress indicators in Holstein calves - Dockweiler, Jenna Corinne (Kansas State University, 2012)
As public concern for food animal welfare increases, the need for objective pain assessment and methods to alleviate pain associated with production practices such as castration gains attention. The aims of this study were (i) to evaluate the physiological response to pain induced by castration in calves and (ii) to elucidate age-related differences in pain response of calves subjected to different castration methods. Seventy six Holstein bull calves were blocked by age (≤ 6 weeks and ≥ 6 months) and randomly assigned to one of four treatment groups: control (n = 20), castration by banding (n = 18), cut and clamp surgical castration (n = 20), and cut and pull surgical castration (n = 18). Measurements included electroencephalogram, heart rate variability, infrared thermography, electrodermal activity, and concentrations of serum cortisol, and plasma substance P prior to, during, and following castration. Electroencephalogram recordings showed desynchronization for all treatments, consistent with increased arousal; yet the magnitude of desynchronization was greatest for 6-month-old calves castrated by cut and clamp. Additionally, older calves in the cut and pull group showed greater desynchronization than younger calves in the same group. Based on the heart rate variability analysis, 6-month-old calves in the control or cut and pull castration groups showed greater sympathetic tone than younger calves in the same treatment groups. Overall, younger calves showed lower electrodermal activity than older calves. Regardless of treatment, concentrations of cortisol and plasma substance P were greater in 6-month-old calves relative to their younger counterparts. In summary, neurohormonal and electroencephalographic stress responses of calves to castration were age-specific. Castration by cut and clamp showed the most pronounced stress response in 6-month-old calves.
Keywords: Calf; Castration; Electroencephalogram; Pain; Agriculture, General (0473); Animal Sciences (0475); Veterinary Medicine (0778)